Epoxidation of waste cooking oil-based palm oil via Prileschajew reaction / Danial Nuruddin Azlan Raofuddin - Azlan Raofuddin, Danial Nuruddin (2023)
In this study, waste cooking oil-based palm oil were choosing as feedstock for epoxidation reaction. At present, there are limited studies on the production of epoxidised waste cooking oil-based palm oil to obtain high relative conversion to oxirane. Epoxides are valuable substances with a wide variety of applications such as plasticizers, adhesives, and lubricants. The epoxidation process of waste cooking oil-based palm oil was carried out using in situ generated performic acid or known as Prileschajew reaction. The first objective was achieved by obtaining the stirring speed at 300 rpm and sulfuric acid as catalyst. Then, the stirring speed and catalyst were used constantly throughout the epoxidation experiments for optimisation. Moving to second objective, Taguchi method of optimisation and analysis of variance (ANOVA) were used to conduct series of experiments around the optimum conditions or parameters.